1993
DOI: 10.1152/jappl.1993.74.5.2105
|View full text |Cite
|
Sign up to set email alerts
|

Products of cyclooxygenase mediate the responses of the guinea pig trachea to hydrogen peroxide

Abstract: The role of products of cyclooxygenase was investigated in the responses of isolated airways to H2O2. Strips of guinea pig trachea, in some of which the epithelium had been removed mechanically, were suspended in organ chambers, and isometric tension was recorded. Under basal conditions, H2O2 induced indomethacin-sensitive contractions, which were larger in preparations without than in those with epithelium; the difference was abolished by inhibitors of thromboxane synthase or thromboxane A2 receptors. During … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
23
1

Year Published

2000
2000
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 12 publications
3
23
1
Order By: Relevance
“…Moreover, it was found that of the two isoforms, the constitutive COX-1 and the inducible COX-2, only the latter is activated by H 2 O 2 (50, 51) and superoxide (50). The COX inhibitor indomethacin relaxed both the intact and epithelium-denuded trachea in the present as well as in the earlier experiments (20). The indomethacin induced relaxation of the intact trachea was significantly larger than that of the epithelium-denuded trachea.…”
Section: Discussionsupporting
confidence: 63%
See 4 more Smart Citations
“…Moreover, it was found that of the two isoforms, the constitutive COX-1 and the inducible COX-2, only the latter is activated by H 2 O 2 (50, 51) and superoxide (50). The COX inhibitor indomethacin relaxed both the intact and epithelium-denuded trachea in the present as well as in the earlier experiments (20). The indomethacin induced relaxation of the intact trachea was significantly larger than that of the epithelium-denuded trachea.…”
Section: Discussionsupporting
confidence: 63%
“…As described earlier, there are species variations among the responses of airways to H2O2: contraction in bovine (21), cat (19) and horse (27) trachea, relaxation in rabbit (17) (also by hydroxyl radical (26)) and dog trachea (18) and biphasic response in guinea pig trachea (16,20). On long lasting contact of tissues with H 2 O 2 , FeSO 4 /H 2 O 2 and FeSO4/ascorbic acid, the contraction not only faded progressively with time but also a significant relaxation appeared, suggesting a biphasic character of the response in the present study.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations